Characterization of Thick Film Capicitors. (1977) - Leroy, Y.; Descamps, M.; Vernet, M.
Abstract : Teaching activities of the "Institut Universitaire de Technologie de Lille" (France) were previously reported. The present paper reports measurement results obtained by students during their last training period for about a hundred capacitors made with commercial dielectrics (EMCA CDP 400, EMCA CDP 2000, and ESL K 1000). We examine the following points: reproducibility of capacitors during fabrication, correlation between electrical parameters of components and firing conditions, measurements of capacitance and loss factor between 10 kHz and 20 MHz for temperatures ranging from 20°C to 100°C.